Descompuneti in factori:
(3x+1)²-(x+3)²
Răspunsuri la întrebare
Răspuns de
19
(3x+1)² - (x+3)² = ( 3x + 1 + x +3) · ( 3x +1 -x - 3) =
= ( 4x + 4) · ( 2x - 2 ) =
= 4 · ( x +1) ·2 · ( x -1 ) =
= 8 · ( x +1 ) · ( x - 1)
= ( 4x + 4) · ( 2x - 2 ) =
= 4 · ( x +1) ·2 · ( x -1 ) =
= 8 · ( x +1 ) · ( x - 1)
Răspuns de
13
(3x+1-x-3)(3x+1+x+3)=(2x-2)(4x+4)-;2(x-1)*4(x+1)=8(x-1)(x+1)
Alte întrebări interesante
Franceza,
9 ani în urmă
Germana,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă